Lunar meteorite Yamato-791197: A polymict anorthositic norite breccia - Lindstrom,Marilyn M.; Lindstrom,David J.; Korotev,Randy L.; Haskin,Larry A. (1986)
P(論文) The lunar origin of Antarctic meteorite Yamato-791197 is confirmed by geochemical and petrologic studies of four subsamples of split 89. The meteorite has a bulk composition of ferroan anorthositic norite with very low incompatible element concentrations. It is a breccia containing clasts of igneous and metamorphic lunar highlands rocks, melt rocks and glasses derived from them by impact, and rare clasts of mare basalt. Y-791197 is similar in composition and clast assemblage to ALHA81005,but there are significant differences between the two meteorites in the ratio of Mg/Fe, concentrations of Sc and REE, and proportions of clast types. These differences are no greater than those observed among breccias ejected by a single lunar impact of modest size (1km crater), so the derivation of Y-791197 and ALHA81005 from a single impact is possible. Regional differences in clast assemblages between Apollo sites are much larger, so the similarities in clast assemblage between the two meteorites support the suggestion that they originated from the same region of the Moon. We conclude that the two meteorites were ejected from the Moon by the same impact. The lunar meteorites are very similar in composition to lunar granulitic breccias and to the estimated average composition of the lunar highlands, unlike most Apollo highlands soils and breccias which are enriched in a KREEP component. The dominance of plutonic anorthositic norite precursors in the granulites and their common occurrence in the lunar meteorites suggest that abundant quantities of anorthositic norites were produced during lunar crustal evolution. departmental bulletin paper